1997
DOI: 10.1111/j.1651-2227.1997.tb18351.x
|View full text |Cite
|
Sign up to set email alerts
|

The fetal origins of coronary heart disease

Abstract: Barker DJP. The fetal origins of coronary heart disease. Acta Paediatr 1997; Suppl42278-82. Stockholm.Animal studies have shown that undernutrition before birth programmes persisting changes in a range of metabolic, physiological and structural parameters. Studies in humans have shown that men and women whose birthweights were at the lower end of the normal range, who were thin or short at birth or small in relation to placental size have increased rates of coronary heart disease. We are beginning to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
506
1
26

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 515 publications
(550 citation statements)
references
References 30 publications
17
506
1
26
Order By: Relevance
“…In 1989, Barker exposed the relationship between birth weight and the lifetime risk for CHD. He showed that the lower the weight of the newborn and during infancy, the higher the risk for CHD in later life, a fact that has been demonstrated in many subsequent studies (15)(16)(17) . The relationship between birth weight and later obesity has been less studied and there is insufficient evidence.…”
mentioning
confidence: 78%
“…In 1989, Barker exposed the relationship between birth weight and the lifetime risk for CHD. He showed that the lower the weight of the newborn and during infancy, the higher the risk for CHD in later life, a fact that has been demonstrated in many subsequent studies (15)(16)(17) . The relationship between birth weight and later obesity has been less studied and there is insufficient evidence.…”
mentioning
confidence: 78%
“…A strand of recent work suggests that nutrition in utero can affect health status in middle age, through its impact on such important chronic conditions as coronary heart disease and diabetes (Barker, 1995;Ravelli et al, 1998). New experimental work finds that mice whose fetal growth is restricted, but who are fed well after birth, exhibit rapid catch-up growth but die significantly earlier than mice well fed in utero (Ozanne and Hales, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The notion that exposure to risk factors in early life in utero or in childhood may causally affect health later in life was first empirically investigated by Barker in relation to the metabolic syndrome, type II diabetes and cardiovascular diseases. Barker suggested that the last trimester of life in utero was a "critical period" which if exposed to growth retardation would eventually result in a number of increased risk factors and diseases related to the metabolic syndrome (Barker, 1995;Barker, 1998). The critical period hypothesis has later been empirically investigated with regard to a variety of diseases other than the metabolic syndrome and its clinical consequences (Sahade et al, 2011).…”
Section: Introductionmentioning
confidence: 99%